Negotiating tradition and modernity: users preferences of souqs and malls in Bahrain - Abid, Nazish; Mestarehi, Motaz; Khalfan, May; Almadhoob, Huda (Frontiers in Built Environment, 2026)
Rapid urbanization in the Arabian Gulf during the late twentieth century introduced innovative architectural and commercial concepts aimed at achieving modernization. In Bahrain, these shifts contributed to the rise of shopping malls, which have overshadowed the cultural and traditional identity of Souqs. Understanding how users perceive and experience these contrasting retail environments is essential for navigating the tension between tradition and modernity. A cross-sectional online survey of 240 Bahraini nationals and expatriates assessed ambience, accessibility, social interaction and cultural identity, using constructs adapted and reworded for the Bahraini context. Data was analyzed with descriptive statistics, principal component analysis, cluster and regression analysis. The analysis revealed that souq users predominantly valued hedonic shopping attributes, emphasizing cultural richness, experiential qualities and social interaction. In contrast, mall users prioritized functional and utilitarian aspects such as convenience, accessibility and environmental comfort. These distinct preferences highlight divergent expectations shaped by contemporary lifestyles and cultural identity, while cluster analysis further identified comfort, culture and hybrid oriented user segments and strong support for hybrid retail spaces. Lastly, Findings indicate coexistence rather than displacement in Bahrain’s retail landscape: users selectively engage both souqs and malls, seeking a mix of utilitarian benefits and culturally meaningful experiences. This underscores the potential of hybrid, context-sensitive retail environments that integrate modern comfort with heritage and social life.